Potentiation of paclitaxel effect by resveratrol in human breast cancer cells by counteracting the 17β‐estradiol/estrogen receptor α/neuroglobin pathway. Issue 4 (13th November 2018) - Cipolletti, Manuela; Montalesi, Emiliano; Nuzzo, Maria Teresa; Fiocchetti, Marco; Ascenzi, Paolo; Marino, Maria
Abstract: Neuroglobin (NGB), an antiapoptotic protein upregulated by 17β‐estradiol (E2), is part of E2/estrogen receptor α (ERα) pathway pointed to preserve cancer cell survival in presence of microenvironmental stressors including chemotherapeutic drugs. Here, the possibility that resveratrol (Res), an anticancer plant polyphenol, could increase the susceptibility of breast cancer cells to paclitaxel (Pacl) by affecting E2/ERα/NGB pathway has been evaluated. In MCF‐7 and T47D (ERα‐positive), but not in MDA‐MB 231 (ERα‐negative) nor in SK‐N‐BE (ERα and ERβ positive), Res decreases NGB levels interfering with E2/ERα‐induced NGB upregulation and with E2‐induced ERα and protein kinase B phosphorylation. Although Res treatment does not reduce cell viability by itself, this compound potentiates Pacl proapoptotic effects. Notably, the increase of NGB levels by NGB expression vector transfection prevents Pacl or Res/Pacl effects. Taken together, these findings indicate a new Res‐based mechanism that acts on tumor cells impairing the E2/ERα/NGB signaling pathways and increasing cancer cell susceptibility to chemotherapeutic agent. Abstract : Res treatment does not reduce cancer cell viability by itself Res interferes with estradiol/estrogen receptor α‐induced NGB upregulation in breast cancer cells This new Res‐based mechanism potentiate cancer cell susceptibility to chemotherapeutic agent